Stroke-Associated Cortical Deafness: A Systematic Review of Clinical and Radiological Characteristics - Gracinda Silva (MDPI AG, 2021)
Background: Stroke is the leading cause of cortical deafness (CD), the most severe form of central hearing impairment. CD remains poorly characterized and perhaps underdiagnosed. We perform a systematic review to describe the clinical and radiological features of stroke-associated CD. Methods: PubMed and the Web of Science databases were used to identify relevant publications up to 30 June 2021 using the MeSH terms: “deafness” and “stroke”, or “hearing loss” and “stroke” or “auditory agnosia” and “stroke”. Results: We found 46 cases, caused by bilateral lesions within the central auditory pathway, mostly located within or surrounding the superior temporal lobe gyri and/or the Heschl’s gyri (30/81%). In five (13.51%) patients, CD was caused by the subcortical hemispheric and in two (0.05%) in brainstem lesions. Sensorineural hearing loss was universal. Occasionally, a misdiagnosis by peripheral or psychiatric disorders occurred. A few (20%) had clinical improvement, with a regained oral conversation or evolution to pure word deafness (36.6%). A persistent inability of oral communication occurred in 43.3%. A full recovery of conversation was restricted to patients with subcortical lesions. Conclusions: Stroke-associated CD is rare, severe and results from combinations of cortical and subcortical lesions within the central auditory pathway. The recovery of functional hearing occurs, essentially, when caused by subcortical lesions.